2022
DOI: 10.3389/fpubh.2022.1017801
|View full text |Cite
|
Sign up to set email alerts
|

Facilitators and barriers in preventing doping among recreational athletes: A qualitative interview study among police officers

Abstract: BackgroundDoping is a societal problem associated with health problems, violence, and other crimes, especially when combined with alcohol and drugs. Elite, as well as recreational athletes who exercise in gyms may use doping to enhance their performance and/or improve their appearance. According to Swedish law, manufacturing, selling, supplying, possessing, and using anabolic androgenic steroids and growth hormones is forbidden. Exceptions apply if these substances are used for medical purposes and prescribed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(8 citation statements)
references
References 38 publications
(112 reference statements)
2
6
0
Order By: Relevance
“…Results showed that most respondents consider doping a societal problem and that doping occurs in combination with several other crimes, such as violence, illicit drug use, and drug dealing. These results are supported by a recent interview study with police officers in Sweden ( 34 ). Almost all respondents also believe it to be their duty to prevent doping but lack proper prerequisites to do so, emphasizing the opinion that there is a lack of knowledge in the police organization.…”
Section: Discussionsupporting
confidence: 80%
See 4 more Smart Citations
“…Results showed that most respondents consider doping a societal problem and that doping occurs in combination with several other crimes, such as violence, illicit drug use, and drug dealing. These results are supported by a recent interview study with police officers in Sweden ( 34 ). Almost all respondents also believe it to be their duty to prevent doping but lack proper prerequisites to do so, emphasizing the opinion that there is a lack of knowledge in the police organization.…”
Section: Discussionsupporting
confidence: 80%
“…Collaboration agreements between gyms and the police, including enabling police officers to exercise undercover in the training premise to detect doping-related crimes, could also, according to the respondents, constitute facilitating factors. This view was previously highlighted in interviews with Swedish police officers ( 34 ). Several respondents also highlighted the importance of more gyms working actively against doping, preferably in line with the 100% PHT doping prevention method, which aligns with suggestions of field experts ( 10 ).…”
Section: Discussionmentioning
confidence: 61%
See 3 more Smart Citations